Levitation of a flexible rotor supported by hybrid magnetic bearings - Nozomu ISHIKAWA (The Japan Society of Mechanical Engineers, 2015)
Recently, it has become necessary for rotors of centrifugal compressors, industrial rolls, and other devices to be less weighted, have a long span, and operate at high rotation speed to increase productivity. Such rotors are more likely to have a high order mode than other types of rotors at the same rotational speed, and may become unstable. To solve this problem, active magnetic bearings are used to support the flexible rotor. However, because a general active magnetic bearing uses bias current to control the bearing force, it consumes a large amount of electricity. To reduce power consumption, a hybrid active magnetic bearing (HAMB) that consists of electromagnets and permanent magnets is used. The HAMB fabricated in this work has negative stiffness in both radial and angular directions. Two HAMBs, one at each end of a flexible rotor arranged horizontally, are installed to levitate it. A PID controller with a notch filter is used to control levitation. With only a PID controller, levitation of the flexible rotor becomes unstable because the flexible mode stimulates vibration. To settle the flexible mode vibrations, the notch filter is designed at the frequency of the flexible mode. Applying the notch filter to the displacement control loop has little effect on vibration decrement, whereas applying it against the angle control loop produces a remarkable effect. Therefore, the notch filter is applied only to the angle control loop. A rotation test is then implemented. The experimental results show that the HAMB-based control system stably passes through the second flexible mode rotation speed. Then, by using the advantage of the HAMB to reduce power consumption effectively, the ability of the system to reduce the control current to use zero power control is demonstrated, and, the results are compared with PID control when levitating the flexible rotor. Furthermore, a levitation test is conducted with linear quadratic regulator control.